Animal health management perspectives of rural livestock farmers in Southwest Nigeria: the place of community based animal health workers (2010)
A case study of a typical community based rural livestock production system in South-west Nigeria was undertaken using participatory epizootiology (PE) to understand local preferences for animal health management practices and observe if there is any justification or place for community based animal health workers (CBAHW ) in rural livestock health and production management. Sheep and goats were the major animals kept by 46.7% of the respondents, followed by chicken (29.3%), dogs (13.3%), ducks (8.0%) and pigs (2.7%). The major health and production problems identified were Pestes des petit ruminants (PPR) (30.0% of respondents), mange (23.0%) and crop destruction (20.0%); while cannibalism by hawks/eagle was the major problem of poultry production as highlighted by rural women (15%). While more respondents (42.7%) rate modern animal health practitioners as more effective than Fulani pastoralists healers (33.67%) and indigenous local healers (25.0%), modern animal health practitioners were described as least truthful/ unreliable (91.7%), less available (91.7%), most expensive (66.7%) and inaccessible (25.0%). On the other hand, indigenous local healers were rated as very available and more accessible (66.7%) while Fulani pastoralist healers were rated as more available and ready to provide veterinary services (58.3%) compared to indigenous local healers (33.3%) and modern animal health practitioners (8.3%). These results are similar to those obtained in other African countries. In conclusion, despite the prevailing professional apathy to the CBAHW concept by influential veterinary authorities in Nigeria, health issues highlighted by the community-based rural livestock farmers could be adequately addressed by CBAHW.